Transcriptomic Response in Pseudomonas aeruginosa towards Treatment with a Kaempferol Isolated from Melastoma malabathricum Linn Leaves - Mourouge Saadi Alwash; Wan Syaidatul Aqma; Wan Yaacob Ahmad; Nazlina Ibrahim (International Journal of Microbiology)
Pseudomonas aeruginosa is one of the main causes of nosocomial infections and is frequently associated with opportunistic infections among hospitalized patients. Kaempferol-3-O-(2′,6′-di-O-trans-p-coumaroyl)-β-D glucopyranoside (KF) is an antipseudomonal compound isolated from the leaves of the native medicinal plant Melastoma malabathricum. Herein, an RNA-seq transcriptomic approach was employed to study the effect of KF treatment on P. aeruginosa and to elucidate the molecular mechanisms underlying the response to KF at two time points (6 h and 24 h incubation). Quantitative real-time PCR (qRT-PCR) was performed for four genes (uvrD, sodM, fumC1, and rpsL) to assess the reliability of the RNA-seq results. The RNA-seq transcriptomic analysis revealed that KF increases the expression of genes involved in the electron transport chain (NADH-I), resulting in the induction of ATP synthesis. Furthermore, KF also increased the expression of genes associated with ATP-binding cassette transporters, flagella, type III secretion system proteins, and DNA replication and repair, which may further influence nutrient uptake, motility, and growth. The results also revealed that KF decreased the expression of a broad range of virulence factors associated with LPS biosynthesis, iron homeostasis, cytotoxic pigment pyocyanin production, and motility and adhesion that are representative of an acute P. aeruginosa infection profile. In addition, P. aeruginosa pathways for amino acid synthesis and membrane lipid composition were modified to adapt to KF treatment. Overall, the present research provides a detailed view of P. aeruginosa adaptation and behaviour in response to KF and highlights the possible therapeutic approach of using plants to combat P. aeruginosa infections.